Pendidikan Mental Santri Melalui Metode Pembelajaran Ilmu Alat di Pondok Pesantren Miftahul Ulum Lirap - Petanahann - Kebumen - Sukataman Sukataman; Syukron Makmun (LPPM IAINU Kebumen, 2022)
Educating and swifting person’s mindset is seriously supposed to be developed. These matters are proposed to be enacted also in education institution including in Islamic boarding school. The mindset of those who stay in boarding school is perceived yet unestablished. Therefore the teaching and learning methods become significant to change students’ mindsets to be more tough and stronger, emerge as a homework for education institution, As MiftahulUlum Lirap Islamic boarding school, Petanahan, Kebumen applied is considered unique and eccentric. The methods are lalaran (study), mempeng (be beyond diligent) and cek (check). the last method mostly examine the psychological aspects , various tests should be taken and the students must concentrate on main focus. Hence the students are challenged through patience, perseverance, strength, passion toward one goal.